Educating water professionals for the Arab world: Archetypes, change agents and complex realities. (December 2020) - Dehnavi, Sudeh; Al-Saidi, Mohammad
Abstract: Water education relevance and courses have grown over the last couple of decades, and incorporated more interdisciplinary and integrated contents. This is due to the increasing relevance of water management issues, particularly in regions with extreme water scarcity such as the Middle East. The concept of Integrated Water Resources Management (IWRM) represents a global consensus on the right way to address water challenges. It has been translated into graduate programs that follow the archetypes of integration (e.g. with energy and land sectors), interdisciplinarity, collaboration and diversity. IWRM programs should also incorporate context specificity, impact orientation and problem-solving using practical and scientific competences. This paper evaluates the implementation challenges of the IWRM agenda in a unique intercultural master program. While such programs are highly relevant for the MENA region, educating change agents in a normative sustainability agenda is challenging. The water sectors in the region are still driven by jobs in the international cooperation field and a lack of appreciation of modern sustainability concepts. The water professions are also dominated by the old paradigms of the engineering based promotion of water resources.